Narodziny polskiej myśli narodowej – z perspektywy włoskiej - Ewa Litwin (Fabrica Litterarum Polono-Italica, 2020)
The article aims to present the work of Daniele Stasi regarding the birth of Polish nationalism. The book was published in 2018 in Italian by FrancoAngeli as Le origini del nazionalismo in Polonia. The author puts forward some theses concerning the process of national building in the period preceding the partitions of Poland, which represents terminus a quo for his analysis of the ideologies related to the national issue and rebirth of Polish state. Terminus ad quem of the author’s analysis is Roman Dmowski’s Myśli nowoczesnego Polaka. Based on rich and interdisciplinary literature, Stasi’s work aims to fill the gap in Italian historiography, related to the birth of Polish nationalism.